1994
DOI: 10.1021/es00053a016
|View full text |Cite
|
Sign up to set email alerts
|

XPS and XANES Studies of Uranium Reduction by Clostridium sp

Abstract: Speciation of uranium in cultures of Clostridium sp. by X-ray absorption near-edge spectroscopy (XANES) at the National Synchrotron Light Source and by X-ray photoelectron spectroscopy (XPS) showed that U(VI) was reduced toU(IV). In addition toU(IV), a lower oxidation state of uranium, most probably U(III), was detected by XANES in the bacterial cultures. Reduction of uranium occurred only in the presence of growing or resting cells. Organic acid metabolites, the extracellular components of the culture medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(115 citation statements)
references
References 15 publications
2
113
0
Order By: Relevance
“…This is because, as reported by Francis et al (1994) and confirmed in this work, cell growth is inhibited by the presence of U(VI).…”
Section: Uranium Reduction By C Acetobutylicum Vegetative Cellssupporting
confidence: 87%
See 3 more Smart Citations
“…This is because, as reported by Francis et al (1994) and confirmed in this work, cell growth is inhibited by the presence of U(VI).…”
Section: Uranium Reduction By C Acetobutylicum Vegetative Cellssupporting
confidence: 87%
“…Cellular culture, growth and sporulation C. acetobutylicum (DSM 792) was obtained from DSMZ. It was grown anaerobically in a medium modified from Francis et al (1994), the main modification being a lower phosphate concentration to avoid uranium precipitation as a uranylphosphate phase. For this reason, we named the modified medium Francis low phosphate (FLP) basal medium, which is composed of (per liter): CaCl 2 , 0.5 g; K 2 HPO 4 , 0.03 g; NH 4 Cl, 0.5 g; MgSO 4 , 0.2 g; FeSO 4 , 2.8 mg; glucose, 5 g; glycerol, 0.25 mL; peptone, 0.1 g; yeast extract, 0.1 g. pH was set at 6.8, and cultures were incubated at 30 C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clostridium spp. were shown to be able to reduce U(VI) (Francis et al, 1994;Madden et al, 2007) and similar populations were also detected in other OR-FRC sediments using glycerol-amended enrichments (Petrie et al, 2003). Clostridium populations were also suggested to be active members of the OR-FRC microbial community through a study of RNA-derived clone libraries (Akob et al, 2007), and low-G þ C bacteria have been isolated from OR-FRC groundwater (Fields et al, 2005).…”
Section: Biotic Associationsmentioning
confidence: 66%